CNR and BER Ranges for the DVB-T2 Reception-Success - Budi Setiyanto; Risanuri Hidayat; I Wayan Mustika; Sunarno Sunarno (Institute of Advanced Engineering and Science, 2017)
DVB-T2 (Digital Video Broadcasting Terrestrial Second Generation) reception requires a sufficient quality of the received signal. CNR (carrier-to-noise ratio) and BER (bit-error-rate) are two of quantities describing the quality. This paper presents the range of each quantity providing a successful reception based on real data obtained by field-measurements. This data was collected from MO (mobile-outdoor) and SI (stationary-indoor) receiving-systems capturing signal sent by some on-air trial transmitters broadcasting services focused on the fixed-receivers. The result indicated that the successful and failed receptions were split into two quite separated (concentrated) ranges of post-decoded BER and therefore a boundary distinguishing them could be prominently defined. In contrast, they were spread in a wide common range of CNR and pre-decoded BER. Furthermore, the boundary that corresponded to this last quantity was ambiguous. In the case of MO reception as numerical examples, the two split ranges of post-decoded BER were less than about 10-5 and more than about 2.7 × 10-4 for the successful and failed receptions, respectively, whereas CNR as high as about 14 dB could be viewed as a soft boundary distinguishing these both reception-success conditions.